2019
DOI: 10.3390/md17020097
|View full text |Cite
|
Sign up to set email alerts
|

Neorogioltriol and Related Diterpenes from the Red Alga Laurencia Inhibit Inflammatory Bowel Disease in Mice by Suppressing M1 and Promoting M2-Like Macrophage Responses

Abstract: Macrophages are central mediators of inflammation, orchestrating the inflammatory response through the production of cytokines and nitric oxide. Macrophages obtain pro-inflammatory (M1) and anti-inflammatory (M2) phenotypes, which can be modulated by soluble factors, including natural products. Despite the crucial protective role of inflammation, chronic or deregulated inflammation can lead to pathological states, such as autoimmune diseases, metabolic disorders, cardiovascular diseases, and cancer. In this ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 28 publications
1
28
0
Order By: Relevance
“…IRAK3 mRNA and protein expression and its effects on inflammation have been studied widely using various experimental models including cell lines [ 10 , 13 , 21 24 ], human or mouse primary cells [ 25 28 ], and animal in vivo models [ 29 31 ], and reported to have contradicting effects on immune responses. Wesche et al .…”
Section: Introductionmentioning
confidence: 99%
“…IRAK3 mRNA and protein expression and its effects on inflammation have been studied widely using various experimental models including cell lines [ 10 , 13 , 21 24 ], human or mouse primary cells [ 25 28 ], and animal in vivo models [ 29 31 ], and reported to have contradicting effects on immune responses. Wesche et al .…”
Section: Introductionmentioning
confidence: 99%
“…In response to pathogen infection, inflammatory reactions are activated through recognizing pathogens by pattern recognition receptors (PPRs) in macrophages, such as toll‐like receptors (TLRs). Disordered inflammatory response is known to be one of the most important causes of autoimmune diseases, such as inflammatory bowel diseases, 1,2 systemic sclerosis, 3 polymyositis, 4 and diabetes 5 . Thus, defining the mechanisms of inflammation regulation is then considered of great importance.…”
Section: Introductionmentioning
confidence: 99%
“…According to the functional characteristics, macrophages are mainly divided into pro-inflammatory macrophages (M1 polarized phenotype) and anti-inflammatory macrophages (M2 polarized phenotype). Previous studies found that macrophages are closely related to the development of IBD (Rubio & Schmidt, 2018;Leonardi et al, 2018;Fries et al, 2013), and it was confirmed that IBD can be alleviated by inhibiting M1 macrophage polarization and promoting M2 macrophage polarization (Daskalaki et al, 2019). Therefore, investigating the molecules that can affect macrophage polarization may provide new targets for IBD therapy.…”
Section: Introductionmentioning
confidence: 85%